2018
DOI: 10.7554/elife.34122
|View full text |Cite
|
Sign up to set email alerts
|

A conserved function for pericentromeric satellite DNA

Abstract: A universal and unquestioned characteristic of eukaryotic cells is that the genome is divided into multiple chromosomes and encapsulated in a single nucleus. However, the underlying mechanism to ensure such a configuration is unknown. Here, we provide evidence that pericentromeric satellite DNA, which is often regarded as junk, is a critical constituent of the chromosome, allowing the packaging of all chromosomes into a single nucleus. We show that the multi-AT-hook satellite DNA-binding proteins, Drosophila m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
138
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(155 citation statements)
references
References 57 publications
(75 reference statements)
9
138
0
Order By: Relevance
“…Our prior study showed that disruption of chromocenter formation in D1 mutants led to micronuclei formation due to lack of chromosome bundling in interphase nuclei, leading to a loss of cellular viability in the Drosophila germline (Jagannathan et al, 2018). Similar to these observations with D1 mutant cells, we observed that mutation of prod resulted in the formation of micronuclei in larval imaginal discs (Figure 2A It is well established that the DNA within micronuclei is prone to genomic instability including excessive levels of DNA damage (Crasta et al, 2012;Hatch et al, 2013).…”
Section: Prod Mutant Cells Exhibit Cellular Phenotypes Associated Witsupporting
confidence: 81%
See 1 more Smart Citation
“…Our prior study showed that disruption of chromocenter formation in D1 mutants led to micronuclei formation due to lack of chromosome bundling in interphase nuclei, leading to a loss of cellular viability in the Drosophila germline (Jagannathan et al, 2018). Similar to these observations with D1 mutant cells, we observed that mutation of prod resulted in the formation of micronuclei in larval imaginal discs (Figure 2A It is well established that the DNA within micronuclei is prone to genomic instability including excessive levels of DNA damage (Crasta et al, 2012;Hatch et al, 2013).…”
Section: Prod Mutant Cells Exhibit Cellular Phenotypes Associated Witsupporting
confidence: 81%
“…
A central principle underlying the ubiquity and abundance of pericentromeric satellite DNA repeats in eukaryotes has remained poorly understood. In our previous study (Jagannathan et al, 2018), we proposed that the interchromosomal clustering of satellite DNAs into nuclear structures known as chromocenters ensures encapsulation of all chromosomes into a single nucleus. Chromocenter disruption led to micronuclei formation, resulting in cell death.
…”
mentioning
confidence: 99%
“…In line with this observation, AHL15 and several of its homologs are upregulated and required for SE induction upon 2,4-D treatment. Furthermore, they are required for efficient BBM-induced SE as downstream targets of BBM.AT -hook motif-containing proteins are generally considered to be chromatin architecture factors17,[30][31][32]47 . Studies in animals have shown that chromatin decondensation precedes the induction of pluripotent stem cells and their subsequent differentiation48 .…”
mentioning
confidence: 99%
“…Moreover, tight chromatin compaction may help in maintaining other heterochromatin features, such as late replication timing. Alternatively, it may contribute to minimizing recombination between sequences by restricting opportunities for interaction (Quivy et al, 2004;Feng et al, 2014;Grob et al, 2014) and by preserving the full chromosome complement within the nucleus (Jagannathan et al, 2018). As CCs potentially play an essential role in organizing euchromatic loops in the 3D space of the nucleus (Fransz et al, 2002), it will be intriguing to explore how CC reorganization during seedling growth impacts the organization of euchromatin in nuclear space and how it contributes to reprogram gene expression patterns during the transition from heterotrophic to autotrophic growth.…”
Section: Impact Of Deficient Replication-coupled Histone Depositionmentioning
confidence: 99%